Deteksi HBsAg dan HBeAg dalam Saliva Pengidap Virus Hepatitis B - Riemawati A. Lesmana (Faculty of Dentistry, Universitas Indonesia, 2015)
Transmission of hepatitis B virus (HBV) via blood or its product has been well established. However, body fluids like urine and saliva may also contain HBV. A complete HBV consists of HBsAg, HBeAg, HBcAg dan partikel DNA. Hepatitis B carrier is detected by the presence of serologic marker HBsAg while the ongoing viral replication or infectivity is diagnosed by the presence of HBeAg or DNA particle. Meanwhile dentists will often contact with the saliva of their patients in daily practice. This cross-sectional study was carried out to assess the infectivity of the saliva of HBV carriers. During a 10 month period (August 1994 - May 1995) detection of HBsAg and HBeAg in blood and saliva were done in 97 HBV carriers using the ELISA method (Enzyme Linked Immunosorbent Assay). Of 97 HBV carriers both positive gor HBsAG in blood were found 56 (Group I) and positive HBsAg and negativa HBeAg in the other 41 (Group II). Examination of the saliva of HBV carriers in Group I showed positive HBsAg as well as HBeAg in 48 (85,7%), only positive for HBsAg in 5 (10,7%) and both negative for HBsAg and HBeAg in the other 2 (3,6%) where as in Group II positive for both HBsAg and HBeAG in the remaining 10 (24,4%). In conclusion, the majority of highly infectious hepatitis B carriers do also have infectious saliva which could be an important source of infection and transmission of the virus in the field of dentistry.